2022
DOI: 10.1098/rspb.2022.1070
|View full text |Cite
|
Sign up to set email alerts
|

Higher phage virulence accelerates the evolution of host resistance

Abstract: Pathogens vary strikingly in their virulence and the selection they impose on their hosts. While the evolution of different virulence levels is well studied, the evolution of host resistance in response to different virulence levels is less understood and, at present, mainly based on observations and theoretical predictions with few experimental tests. Increased virulence can increase selection for host resistance evolution if the benefits of avoiding infection outweigh resistance costs. To test this, we exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…In a previous study (Wendling et al, 2022) we found that in the presence of Vibrio phage VALGΦ8 the bacterium V. alginolyticus K01M1 evolved phage resistance by modifying the viral binding site. These mutants rapidly replaced phage-carriers, which were resistant due to super infection exclusion (SIE)-immunity.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a previous study (Wendling et al, 2022) we found that in the presence of Vibrio phage VALGΦ8 the bacterium V. alginolyticus K01M1 evolved phage resistance by modifying the viral binding site. These mutants rapidly replaced phage-carriers, which were resistant due to super infection exclusion (SIE)-immunity.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study (Wendling et al, 2022), we found two alternative defence strategies conferring resistance against the co-evolving filamentous Vibrio phage VALGΦ8: (1) superinfection exclusion (SIE) resulting from the presence of the co-evolving phage in the bacteria cell or (2) surface receptor mutations (SRM) in the MSHA type IV pilus preventing phage attachment. To quantify the frequency of co-evolving strains that acquired resistance by superinfection exclusion, we used colony PCR with a primer pair that specifically targets a unique region in the co-evolving Vibrio phage VALGΦ8 following a previous protocol (Wendling et al, 2022). PCR-bands at a length of 1.2 kbp were interpreted as presence of VALGΦ8 in the bacterial cell indicating SIE.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations